Resolving Office Establishment Dispute in Nigeria through Alternative Dispute Resolution Mechanism: An Evolving Regime - Bosede Remilekun Adeuti (Sriwijaya Law Review, 2021)
This paper examines contemporary issues in Office Establishment Dispute Resolution Mechanism in Nigeria. It explores strategic ways of resolving such office establishment dispute which has remained an intractable problem in Nigeria. The objective is to examine litigation challenges in settlement of this office dispute in Nigeria and other developing countries. This paper argues that adopting Alternative Dispute Resolution Mechanism in Office Establishment Dispute is not only a programmatic goal to be attained in the long term but rather an immediate obligation that is preferable to litigation in the court of law. The doctrinal research methodology will be used to examine the challenges in resolving office establishment dispute through alternative dispute resolution Mechanisms. This paper adopts an analytical and qualitative approach and builds its argument on existing literature works, which are achieved by synthesising ideas. Recommendations and suggestions are made based on research findings.  This paper concludes that the era of jettisoning or sacrificing Alternative Dispute Resolution on the altar of inapplicability in resolving office establishment dispute is gone and the need to move with time with the practise which has been in existence in developed countries for decades.